Mastering WordPerfect 9 - Simpson, Alan, 1953- (SYBEX, 1999)
"Whether you're new to WordPerfect or already an experienced user, you won't find a more valuable resource than Mastering WordPerfect 9. This book offers comprehensive, crystal-clear coverage of standard features, the latest improvements, and the most advanced techniques - you'll find hundreds of surefire ways to improve the quality of your documents. If you want to be an efficient WordPerfect user and get the most out of the newest release, you've come to the right source."--BOOK JACKET.